Are mandibular overdentures retained by one implant associated with higher patient satisfaction? A systematic review - Sampaio, André Luis Venâncio; Gomes, Jéssica Marcela de Luna; Pereira, Maurício Veríssimo; Limírio, João Pedro Justino de Oliveira; Pellizzer, Eduardo Piza (ARCHIVES OF HEALTH INVESTIGATION, 2025)
Objective: Aimed to evaluated if mandibular overdentures retained by one implant provide the same level of patient satisfaction when compared to those retained by two implants. Methods: This systematic review was registered on PROSPERO (CRD42024585772) and follows the PRISMA checklist. The PICO was: “Are mandibular overdentures retained by one implant associated with higher patient satisfaction compared to those retained by two implants?”, “P” were patients using mandibular overdentures, “I” was the using of mandibular overdentures retained by a one implant, “C” was the using of overdentures retained by two implants and “O” was patient satisfaction. The search was carried out in PubMed/Medline, Cochrane Library and Embase databases. RoB 2 scale was used to determine the risk of bias and GRADE approach was used to assessed the quality of the evidence. Results: The databases search retrieved 2408 studies. After removing duplicates and reading the full five studies were considered eligible. According to RoB 2 scale there was a predominance of low risk of bias among the seven domains. According to the GRADE approach no large effect was observed in the included studies. Conclusion: The use of one implant in mandibular overdenture is a clinical approach viable with good patient satisfaction.